Hereditary angioedema (HAE): a cause for recurrent abdominal pain. (14th November 2016) - Soni, Parita; Kumar, Vivek; Alliu, Samson; Shetty, Vijay
Abstract : A 44-year-old Hispanic woman presented to the emergency room with a 2-day history of sudden onset of severe cramping left lower quadrant abdominal pain associated with ∼20 episodes diarrhoea. Abdominal CT scan exhibited bowel wall oedema and acute extensive colitis. On the basis of the preliminary diagnosis of acute abdomen, the patient was admitted under the surgical team and treated for acute colitis. Since her family history was significant for hereditary angioedema (HAE), complement studies were performed which revealed low complement C4 levels and abnormally low values of C1q esterase inhibitor. Thus, the diagnosis of HAE type I was established. This case report summarises that the symptoms of HAE are often non-specific, hence making the underlying cause difficult to diagnose.